Pengelolaan Sarana dan Prasarana Perpustakaan untuk Meningkatkan Kualitas Pembelajaran di MTS YPAK Cigugur - Ajeng Tanjiah Mukti; Deti Kurnia; Misbahhudin Misbahhudin; Tatin Suhertin; Uswatun Hasanah; Yayat Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This research aims to determine the management of library facilities and infrastructure at MTs YPAK Cigugur. Second, knowing about library management in improving the quality of learning at MTs YPAK Cigugur. This research is qualitative research using observation, interviews, and documentation as data collection techniques. Research location at MTs YPAK Cigugur. The results of the research show that library management is not optimal in fostering the quality of learning and interest in reading of students at MTs YPAK Cigugur. This is evidenced by the facilities and infrastructure which are still far from the ideal library concept and library standards, where the room for the library is not spacious enough and the facilities in the library are not complete, there is only 1 table and chair, 1 bookshelf, and 2 cupboards which only contain books. - books that have been damaged, causing children to be less interested in coming to the library, which causes them to prefer reading in the classroom rather than in the library. The benefit of this research is to help the YPAK Cigugur MTs school find the right solution to make the library a learning place for students so that students can understand the meaning of reading in the library room.